Science toys - White, Laurence B.; Brown, Marc Tolon (Reading, MA : Addison-Wesley, 1975)
Directions for some simple projects, such as a mold garden, a shadow clock, and an air spinner, that demonstrate basic scientific principles.
"An Addisonian Press book."
13 26
Keywords: Science -- Experiments; Science -- Experiments -- Juvenile literature